INFLUENCE OF ENRICHED PRESSMUD COMPOST ON NUTRIENT AVAILABILITY, GROWTH AND YIELD OF RICE (ORYZA SATIVA L.) - D. KALAIVANAN; K. OMAR HATTAB (The Bioscan, 2015)
An investigation was conducted to investigate the effect of enriched pressmud compost prepared from sugar industry was teon soil nutrient availability, growth, yield parameters and yield of rice (Oryza sativa L.). The application of 1.25 t ha-1 of enriched pressmud compost recorded higher straw and grain yields and it was comparable with 2.50 t ha-1 of enriched pressmud compost. The hybrid ADTRH 1 manifested higher grain and straw yield whereas the variety ADT 43 and ADT 36 registered lower grain and straw yields, respectively.Application of 1.25 t ha-1 and 2.50 t ha-1 of enriched pressmud compost were at par with respect to registering maximum plant height, number of tillers, number of productive tillers and dry matter production. Nutrient availability, yield parameters viz., number of grains per panicle and 1000 grain weight and efficiency parameters viz., agronomic efficiency and apparent N recovery were at higher levels and comparable with application of 1.25 t ha-1 and 2.50 t ha-1 of enriched pressmud compost, whereas it was lower with control. Hence, the incorporation of 1.25 t ha-1 enriched pressmud compost as basal along with required remaining nitrogen through inorganic fertilizer as top dressing in three splits may be recommended for rice crop to realize maximum yield in (Kharif) season.